Concerns and Returns to Work in Patients with Breast Cancer Receiving Outpatient Chemotherapy: a Pilot Study - Saori Tamura; Koichi Sakaguchi; Ryuya Yamanaka (Asia-Pacific Journal of Oncology Nursing, 2019)
Objective: Breast cancer survivors are increasing in number among survivors of all types of cancer, and survivors returning to work are extremely important. The development of outpatient chemotherapy has increased the working population of patients undergoing cancer therapy. Consequently, a significant number of breast cancer survivors experience physical, psychological, and social problems. This study aimed to clarify differences in concerns among patients with breast cancer receiving outpatient chemotherapy according to their employment status. Methods: Twenty-eight patients with breast cancer undergoing outpatient chemotherapy were recruited. A questionnaire was used to survey the attributes, employment status, and levels of concern in these patients based on the Cancer-chemotherapy Concerns Rating Scale (CCRS). Data from three groups (employed full time, employed part-time, and unemployed) were analyzed using multiple comparison tests. Results: The patients' mean age was (55.1 ± 9.9) years. According to the CCRS findings, the following three parameters differed between the three groups: scores for the items “I always think about my disease” (employed vs. unemployed, P = 0.005) and “I can't work (housework/schoolwork)” (employed full time vs. part time, P = 0.045), and scores for the “self-existence” subscale (employed vs. unemployed, P = 0.024). Conclusions: This study revealed the characteristics of concerns in patients with breast cancer according to their employment status. Being able to continue working is considered to enhance the social health of these patients. Predicting concerns in employed patients will help gain perspective in early nursing interventions.